Perkembangan Pendidikan Islam Pada Masa Dinasti Umayyah - Nurlaila Nurlaila; Muhammad Zalnur; Zulmuqim Zulmuqim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The aim of this research is to explore in more depth the aspects of Islamic education in the Dinasti Umayyah era. This research uses the library research method, namely using library materials as the main data source in exploring information from the concepts of previous experts. The results of the research show that among the achievements of civilization is the educational aspect which has grown to develop well. Education grew and developed along with the development of Islam, showing its connection to its history. The Dinasti Umayyah, as the first dinasti in the century of expansion, was involved in conquest, consolidation, and forming a multinasional and multicultural empire. They consciously pay attention to educational issues which result in the growth of various scientific treasuresThe impact was felt especially in the European world, where the Dinasti Umayyah succeeded in reclaiming and developing this heritage, which we in Indonesia can also feel.